The effect of mindfulness therapy in acromegaly, a pilot study. (28th November 2022) - Santos, Alicia; Nalin, Chiara; Bortolotti, GianMario; Dominguez‐Clave, Elisabet; Daniela, Gianola; Cortesi, Liana; Pagani, Marina; Momblan, Maria A. M.; Gich, Ignasi; Webb, Susan M.; Trevisan, Roberto; Resmini, Eugenia
Abstract: Background: Patients with acromegaly have often several comorbidities, including decreased quality of life, mood alterations and chronic pain. Mindfulness is effective at improving mood, quality of life and pain management; however, there is no data available on its effect in patients with acromegaly. Objective: We aimed at evaluating changes in quality of life, mood, pain, sleep, self‐compassion, life satisfaction, blood pressure and heart rate after a mindfulness program. Design and Patients: This was a randomized, multicentre, international clinical trial (Barcelona‐BCN and Bergamo‐BG) of 60 patients, 30 per centre. Measurements: The intervention group participated in an 8‐week face‐to‐face group program; the control group followed normal clinical routine. In BG, patients performed a classic Mindfulness Based Stress Reduction program; in BCN they performed an adapted program including elements of mindfulness and compassion with a greater focus on daily life. Results: In the BCN intervention group there was an increase in night‐time hours in bed (p = 0.05) after the program. In both centres there was a trend to a reduction of the time to start sleeping (p = 0.06 BCN, p = 0.07 BG). In BCN, the intervention group reduced the pain score compared to the control group (p = .02), and an improvement in self‐compassion was found (p = .04). In both centres, heart rate decreased significantly in the intervention group during a single 2‐hour session. This was evidenced at the first and the last program session (BCN p = .013 and p = .009; BG < 0.001 and p = .04). A training effect was found in BG, where heart rate fell more in the last session than in the first (p = 002). Conclusions: We have demonstrated for the first time the value of a mindfulness program in patients with acromegaly, analysing possible effects and advantages, and clarifying the usefulness of a specific protocol for the disease.